Familiar fixes for a modern malady: a discussion on the possible cures of COVID-19 - Amrit Krishna Mitra (AIMS Molecular Science, 2020)
The SARS-CoV-2 virus emerged in December 2019 in Wuhan, China and then spread rapidly all over the world. Scientists are intensifying their research efforts in order to find antivirals specific to the virus and vaccines to treat or prevent COVID-19. Now, for a medicative cure for COVID-19, several drugs such as chloroquine, hydroxychloroquine, lopinavir, ritonavir, remdesivir and favipiravir are currently undergoing clinical studies. Convalescent plasma therapy and high dose of intravenous (IV) vitamin C have also been used to treat SARS-CoV-2 infections. This article outlines aspects related to several antiviral drugs and therapies which may be potentially effective against SARS-CoV-2.